Block of A1 astrocyte conversion by microglia is neuroprotective in models of Parkinson's disease. (July 2018) - Yun, Seung; Kam, Tae-In; Panicker, Nikhil; Kim, SangMin; Oh, Yumin; Park, Jong-Sung; Kwon, Seung-Hwan; Park, Yong; Karuppagounder, Senthilkumar; Park, Hyejin; Kim, Sangjune; Oh, Nayeon; et al.
Abstract Activation of microglia by classical inflammatory mediators can convert astrocytes into a neurotoxic A1 phenotype in a variety of neurological diseases1, 2 . Development of agents that could inhibit the formation of A1 reactive astrocytes could be used to treat these diseases for which there are no disease-modifying therapies. Glucagon-like peptide-1 receptor (GLP1R) agonists have been indicated as potential neuroprotective agents for neurologic disorders such as Alzheimer's disease and Parkinson's disease3–13 . The mechanisms by which GLP1R agonists are neuroprotective are not known. Here we show that a potent, brain-penetrant long-acting GLP1R agonist, NLY01, protects against the loss of dopaminergic neurons and behavioral deficits in the α-synuclein preformed fibril (α-syn PFF) mouse model of sporadic Parkinson's disease14, 15 . NLY01 also prolongs the life and reduces the behavioral deficits and neuropathological abnormalities in the human A53T α-synuclein (hA53T) transgenic mouse model of α-synucleinopathy-induced neurodegeneration16 . We found that NLY01 is a potent GLP1R agonist with favorable properties that is neuroprotective through the direct prevention of microglial-mediated conversion of astrocytes to an A1 neurotoxic phenotype. In light of its favorable properties, NLY01 should be evaluated in the treatment of Parkinson's disease and related neurologic disorders characterized by microglial activation. Agonism of microglial glucagon-like peptide-1 receptor (GLP1R) using a brain-penetrant peptide prevents the generation of neurotoxic astrocytes and ameliorates disease progression in two rodent models of Parkinson's disease.